Ethical Principles in Biological Research - Andi Basliahwanti Murti; Devi Alvionita; Abdul Rasyid Fakhrun Gani (Undiksha, 2021)
Science has developed from time to time. The development of science is in the hands of a scientist. A scientist must always think, research, and develop science according to his field. In addition, so that the knowledge he develops is beneficial to humanity. The principles of scientific ethics in the biological sciences are autonomous, not harmful, beneficial, and fair to living things. The application of scientific ethical principles in the development of science can be exemplified in research using experimental animals, where scientists must consider and apply a code of ethics for the use of experimental animals, namely reduction, replacement, and refinement. Scientific ethics also plays a role in reviewing the development of the science of human cloning and chimeras so that whatever is done is for the good and welfare of humans and does not cause controversy. The author makes this article aims to determine the relationship between ethics and philosophy of science, to know the principles of bioethics, and to know what are the ethical principles in the application of science, especially biological science.